TCR α+β+/CD19+ cell–depleted hematopoietic stem cell transplantation for pediatric patients. (4th July 2019) - Mitchell, Richard; Cole, Theresa; Shaw, Peter J.; Mechinaud, Francoise; O'Brien, Tracey; Fraser, Chris
Abstract: TCR α + β + /CD19 + cell depletion is an emerging technique for ex vivo graft manipulation in HSCT. We report 20 pediatric patients who underwent TCR α + β + /CD19 + cell–depleted HSCT in four Australian centers. Conditioning regimen was dependent on HSCT indication, which included immunodeficiency (n = 14), Fanconi anemia (n = 3), and acute leukemia (n = 3). Donor sources were haploidentical parent (n = 17), haploidentical sibling (n = 2), or matched unrelated donor (n = 1). Mean cell dose was 8.2 × 10 8 /kg TNC, 12.1 × 10 6 /kg CD34 + cells, and 0.4 × 10 5 /kg TCR α + β + cells. All patients achieved primary neutrophil and platelet engraftment, with average time to neutrophil engraftment 11 days (range 8‐22) and platelet engraftment 24 days (range 12‐69). TRM at 1 year was 15%. Rate of grade II‐IV aGVHD at 1 year was 20% with no grade III‐IV aGVHD seen. CMV reactivation occurred in 81% of CMV‐positive recipients, with one patient developing CMV disease. Average time to CD4 recovery (>400 × 10 6 /L) was 258 days. Overall survival for the cohort at 5 years was 80%. This report highlights the initial experience of TCR α + β + /CD19 + cell–depleted HSCT in Australian centers, with high rates of engraftment, low rates of aGVHD, and acceptable TRM.